"Losers" and "Winners": Framing of online self-disclosure in online news media. Issue 5 (20th October 2017) - Ashuri, Tamar; Halperin, Ruth
ABSTRACT: The intensification of online disclosure of personal information, coupled with the ability to link personal information to those who disclose it, poses important questions regarding the benefits and risks associated with sharing of personal data. This article examines the manifestation of these concerns in news media. Guided by framing theory, it seeks to ascertain the prevailing frames for personal information sharing and to determine whether such framing facilitates debate on issues related to self-disclosure. Articles published in top Israeli online newspapers were analyzed ( n = 609). Findings show that the individual user, the state, and corporations are framed as key actors that shape online self-disclosure practices and their outcomes. Furthermore, the individual user, while portrayed as chief actor, is seen as the weakest player.